Assessing the skills gap for industrial operators in industry 5.0 - Sashidharan, Vaishnavi; Eimontaite, Iveta; Fletcher, Sarah (Springer, 2025)
The following paper presents a study that investigates the existence of a skill gap for operators of Industry 5.0. This study is part of the CONVERGING project, a project that aims to develop and deploy smart-production systems for different industrial use cases. In each use case, a manually performed task is being redesigned as a smart-production system that leverages collaboration between human operators and smart machines such as collaborative robots. The current study’s aim is twofold – firstly, to identify the current skill set of the operators and the skills expected from them to perform the future roles in the smart-production systems. This was achieved through a literature review, hierarchical task analysis and task decomposition. The second aim is to assess whether there is a gap between operators’ current skills and the skills expected from them for performing roles in the future systems. To meet the second aim, an online survey was developed using the list of skills already identified for the first aim, and the survey was administered to use case supervisors and managers. The following paper details the methodology for skill identification and survey development and the results from the survey are discussed.
Keywords: 40 Engineering; 33 Built Environment and Design; 3302 Building; 9 Industry, Innovation and Infrastructure; skills; soft skills; technological skills; technical skills; Industry 5.0; smart technologies